On the Pore-Scale Modeling and Simulation of Reactive Transport in 3D Geometries. Issue 5 (3rd September 2017) - Iliev, Oleg; Lakdawala, Zahra; Neßler, Katherine H.L.; Prill, Torben; Vutov, Yavor; Yang, Yongfei; Yao, Jun
Abstract: Pore-scale modeling and simulation of reactive flow in porous media has a range of diverse applications, and poses a number of research challenges. It is known that the morphology of a porous medium has significant influence on the local flow rate, which can have a substantial impact on the rate of chemical reactions. While there are a large number of papers and software tools dedicated to simulating either fluid flow in 3D computerized tomography (CT) images or reactive flow using porenetwork models, little attention to date has been focused on the pore-scale simulation of sorptive transport in 3D CT images, which is the specific focus of this paper. Here we first present an algorithm for the simulation of such reactive flows directly on images, which is implemented in a sophisticated software package. We then use this software to present numerical results in two resolved geometries, illustrating the importance of pore-scale simulation and the flexibility of our software package.